Soil inorganic carbon in mangroves of tropical China: patterns and implications. (30th November 2018) - Guan, Wei; Xiong, Yanmei; Liao, Baowen
Abstract : Soil inorganic carbon (IC) is neglected in most blue carbon studies despite the globally significant role of the calcium carbonate cycle in ocean C balance and climate change. We sampled soils to 1 m depth from seven mangrove reserves in Hainan Island, China. Only 45 out of 509 samples were rich in IC (greater than 10 mg cm −3 ). Most of the IC-rich samples were found at the outer part of Qinglan Bay, which is adjacent to the largest coral reef zone of Hainan Island. Soil IC concentration ranged from 0 to 66 g kg −1 (or 0–67 mg cm −3 ), accounting for 0–92% of total C. IC concentration increased with soil depth where it was abundant. Soil pH was low (2.36–6.59) in IC-depleted soils, but increased to 5.67–7.99 in IC-rich soils. Soil total C stock and IC stock in mangroves of Hainan amounted to 0.76×10 6 and 0.12×10 6 Mg, respectively, with IC accounting for 16% of total C. Our study finds that carbonate concentrations can be high in mangrove soils but their spatial distribution indicates they are largely allochthonous in origin. Evidence of carbonate dissolution in mangroves suggests mangroves may increase total alkalinity to buffer acidification in seawater.